2009
DOI: 10.1007/s10157-009-0159-5
|View full text |Cite
|
Sign up to set email alerts
|

Current status and issues of C1q nephropathy

Abstract: C1q nephropathy, first proposed by Jennette and Hipp [Am J Clin Pathol 83:415-420, 1985; Am J Kidney Dis 6:103-110, 1985], was described as a distinct glomerular disease entity characterized by extensive mesangial deposition of C1q, with associated mesangial immune complexes, and the absence of any clinical and laboratory evidence of systemic lupus erythematosus. Now, 20 years since the first report, the disease entity is gradually attaining recognition, particularly in the field of pediatrics. C1q is the subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…A rapid decline in serum creatinine and proteinuria was seen following therapy with rituximab, so that hemodialysis could be stopped, and prednisone tapered laboratory evidence of SLE. Clinical manifestations range from asymptomatic proteinuria and/or hematuria with normal renal function to severe nephrotic syndrome with variable progression to ESRD [1,3,9,10]. Our two patients depict this heterogeneity; one an adolescent with moderate renal impairment and massive proteinuria, and the other an elderly woman with rapidly progressive glomerulonephritis necessitating dialysis.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A rapid decline in serum creatinine and proteinuria was seen following therapy with rituximab, so that hemodialysis could be stopped, and prednisone tapered laboratory evidence of SLE. Clinical manifestations range from asymptomatic proteinuria and/or hematuria with normal renal function to severe nephrotic syndrome with variable progression to ESRD [1,3,9,10]. Our two patients depict this heterogeneity; one an adolescent with moderate renal impairment and massive proteinuria, and the other an elderly woman with rapidly progressive glomerulonephritis necessitating dialysis.…”
Section: Discussionmentioning
confidence: 71%
“…Our two patients depict this heterogeneity; one an adolescent with moderate renal impairment and massive proteinuria, and the other an elderly woman with rapidly progressive glomerulonephritis necessitating dialysis. Morphologically, two variants of C1qN have been described, the minimal change disease (MCD) or focal segmental glomerulosclerosis (FSGS) variant and the immune complex glomerulonephritis (GN) variant [1,10]; however, the pathogenesis and role of C1q in this lesion are unclear. In one series, Markowitz et al [3] described C1qN in 19 renal biopsies, of which 17 also demonstrated FSGS including 6 with CG, and 2 had MCD features; they suggested C1qN is a variant of FSGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-localization of C1q and IgG suggests that mesangial deposition is likely Fc-mediated, although direct cell surface interactions or non-specific trapping cannot be excluded. It has been argued that the heterogeneity of histological findings seen by light microscopy in C1q nephropathy is similar to that found in IgA nephropathy, and thus the pathological classification should be determined largely on the basis of C1q staining [11,34]. While the comparison may prove to be an apt one, the acceptance of IgA nephropathy as a distinct clinicopathological disease was facilitated by the high incidence of IgA nephropathy, the publication of an exceptional number of manuscripts on the clinical and pathological aspects of IgA nephropathy (there were nearly 2,000 publications on IgA nephropathy within 25 years of the initial description by Berger), experimental structural data supporting the direct pathogenic role of IgA, as well as animal models, although these have been shown to have limited homology to human disease [68][69][70][71][72].…”
Section: Resultsmentioning
confidence: 98%
“…The purpose of this review is to evaluate potential pathogenic mechanisms underlying C1q nephropathy and provide a current appraisal of the published case series from a pediatric perspective. For a broader discussion of C1q nephropathy the reader is referred to recent papers by Mii et al and Vizak et al [11,12].…”
Section: Introductionmentioning
confidence: 97%